(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Progress in direct laser marking when processing plastics with unmatched quality of markings, contrast and speed. This article presents the latest generation of laser materials and laser equipment systems. When properly applied, laser marking can provide quality for production and add value to the appearance and function of the product.Describe the parameters influencing the depth of the laser marking of polymethylmethacrylate (PMMA) products. Experimental results are presented for determining the quality of cuts on the polymer surface at specific parameters - power and speed.